SICLOPPS: genetic system for production of backbone cyclized peptides - Savinov, Sergey (Henry Stewart Talks, 2008)
SICLOPPS: method for production of genetically encoded backbone cyclized peptides, Cyclic peptides as probes of biological function, Splicing of a circularly rearranged split-intein, Production and isolation of backbone cyclic peptides, Generation of combinatorial libraries, Selection of protein-protein inhibitors using a bacterial two-hybrid assay, Biochemical characterization of dissociative inhibitors
Archived at 2021/02/25